"To Keep What Was Good and Pass it on": George Elliott's Small Town Memorial, The Kissing Man - Lynch, Gerald (Studies in Canadian Literature, 1997)
George Elliott's The Kissing Man anatomizes a small town, looking at the characters, institutions, and traditions that give a place coherence over time. This essay has a threefold purpose: to direct critical attention to this deserving work, to contextualize The Kissing Man in the continuums of the Canadian short story cycle and magic realism generally, and to offer a close reading of some key stories of the cycle, showing the ways they create symbols and rituals that enable the memories and create the meanings which Elliott envisioned as definitive of life in an unnamed southwestern Ontario small town at the middle of the twentieth century.